TOWARDS DISASTER-READY STUDENTRY: IMPROVING PERFORMANCE IN ANALYZING POTENTIAL EARTHQUAKE HAZARDS THROUGH FIT LEARNING ACTIVITY SHEET: TOWARDS DISASTER-READY STUDENTRY: IMPROVING PERFORMANCE IN ANALYZING POTENTIAL EARTHQUAKE HAZARDS THROUGH FIT LEARNING ACTIVITY SHEET - DESEMRADA, JOVI (International Journal of Arts, Sciences and Education, 2022)
The study focused on the enhancement of the academic performance of Science, Technology, Engineering and Mathematics learners in analyzing the effects of the different earthquake hazards using FIT (Feel the ImpacT) Learning Activity Sheet. The research was conducted in Cagayan National High School during the school year 2020-2021 following the pretest-posttest experimental research design. The proponent taught the lesson to both control and experimental groups through virtual class. The experimental group received the intervention FIT Learning Activity Sheet. The proponent then administered a posttest made parallel with the pretest. Assessment tool was based on the Disaster Readiness and Risk Reduction Curriculum Guide following the developed table of specifications which was evaluated by the proponent’s immediate supervisor. After the given intervention, there is a significant difference in the mean posttest scores of the two groups. Additionally, data analysis shows that there is a significant increase in the mean pretest and mean posttest scores of the experimental group. The intervention did enhance, with a very large effect, the learners’ academic performance in analyzing the effects of the different earthquake hazards. The study suggests that the use of FIT Learning Activity Sheet may enhance the learning process of learners in concerned topic in DRRR. Keywords: Earthquake hazards